2019
DOI: 10.1016/j.neo.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

AsiDNA Treatment Induces Cumulative Antitumor Efficacy with a Low Probability of Acquired Resistance

Abstract: The Achilles heel of anticancer treatments is intrinsic or acquired resistance. Among many targeted therapies, the DNA repair inhibitors show limited efficacy due to rapid emergence of resistance. We examined evolution of cancer cells and tumors treated with AsiDNA, a new DNA repair inhibitor targeting all DNA break repair pathways. Effects of AsiDNA or Olaparib were analyzed in various cell lines. Frequency of AsiDNA- and olaparib-resistant clones was measured after 2 weeks of continuous treatment in KBM7 hap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…Actually, transcriptome analysis revealed a major change in gene expression with a large excess of genes down‐regulated in 3 independent “evolved” populations as compared to three independent “naïve” populations (Table ; access to raw data in GEO; GSE144023). A similar bias to repressed expression was observed in MDA‐MB‐231 tumors xenografts after three cycles of AsiDNA injection (Jdey et al, 2019). Strikingly, metabolic pathways were significantly deregulated in “evolved” cells as compared to “naïve” cells analyzed from cell culture or from tumors.…”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…Actually, transcriptome analysis revealed a major change in gene expression with a large excess of genes down‐regulated in 3 independent “evolved” populations as compared to three independent “naïve” populations (Table ; access to raw data in GEO; GSE144023). A similar bias to repressed expression was observed in MDA‐MB‐231 tumors xenografts after three cycles of AsiDNA injection (Jdey et al, 2019). Strikingly, metabolic pathways were significantly deregulated in “evolved” cells as compared to “naïve” cells analyzed from cell culture or from tumors.…”
Section: Resultssupporting
confidence: 60%
“…Indeed, poly(ADP‐ribose) polymerase (PARP) inhibitors, which have been tested for many years and have become a potential supplement to conventional chemotherapy, show increasing evidence of the appearance of resistance during treatment (Kim et al, 2017). In a recent work, it was reported that continuous or cyclic treatments with AsiDNA are much less prone to promote resistance emergence than regular DNA repair inhibitors (Herath et al, 2019; Jdey et al, 2019). In contrast, treated populations showed increased sensitivity to AsiDNA.…”
Section: Introductionmentioning
confidence: 99%
“…γH2AX foci formation at DSB sites can recruit other DSB signalling and repair factors such as MDC1, 53BP1 and the MRN complex to the damage site. 25 Over the past several years, γH2AX expression has been established as a very sensitive surrogate biomarker of DSBs, mostly following radiation-less literature exists about CT. 8,18,[26][27][28] γH2AX expression remains phosphorylated if the DSBs are not repaired due to defects in the DSB repair machinery. Preclinical data in tumour showed that the AsiDNA-induced false damage signalling of γH2AX, phosphorylated Hsp90 and PARP activation significantly increased between 15 and 48 h after each AsiDNA administration and could be considered as early biomarkers of activity.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17] AsiDNA was shown to induce cumulative antitumour activity with low probability of acquired resistance in preclinical models. 18 In the clinic, the drug was first investigated in 23 patients with skin metastases of melanoma in a Phase 1 dose-escalation study, 19 which evaluated the safety and pharmacokinetics (PK) of AsiDNA administered by SC (IT/ peri-tumoural) injections in combination with palliative RT. This first-in-human study of AsiDNA was conducted as a proof of concept of the ability of the drug to sensitise and improve RT response rate (estimated about 10% of complete response rate in melanoma) based on preclinical data showing an AsiDNAinduced radio-sensitisation in human melanoma xenografted models.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it seems to delay the onset of resistance. Actually, whereas olaparib and carboplatin long-term treatments have a high risk of favoring growth of resistant clones in tumor, AsiDNA monotherapy, thanks to its original mechanism of action, seems to be less prone to such events (32). The combination of AsiDNA with carboplatin prevents the emergence of resistant cells in the chemosensitive BC227 cell line.…”
Section: Discussionmentioning
confidence: 99%